Genetic Counseling in a Case of a Pregnant Woman with Goldenhar Syndrome (Oculoauriculovertebral Spectrum) - Yazıcıoğlu, Aslıhan; Yücel, Özge Senem; Selçuk, İlker; Boyraz, Gökhan; Turğal, Mert; Özyüncü, Özgür; Balcı, Sevim; Beksaç, Sinan (Gynecology Obstetrics & Reproductive Medicine, 2012)
Goldenhar Syndrome also known as oculoauriculovertebral spectrum (OAVS) is a rare syndrome characterized by hemifacial microsomi, microtia, epibulbar dermoids, ear malformations and hemivertebrae. The mode of inheritance is clearly unknown and mostly polygenic etiology. The aim of this presentation is to present this young mother with oculoauriculovertebral spectrum and related problems. Most of the individuals with this syndrome do not notice themselves before the time of diagnosis. For that reason, we followed this patient’s pregnancy and performed cesarian section due to cephalopelvic disproportion. The enlighting of these patients with this syndrome is very important for the evaluation of this family and for the future pregnancies.